2021
DOI: 10.1186/s12917-021-02889-8
|View full text |Cite
|
Sign up to set email alerts
|

Immune response in dairy cattle against combined foot and mouth disease and haemorrhagic septicemia vaccine under field conditions

Abstract: Background Foot-and-mouth disease (FMD) and Haemorrhagic septicemia (HS) are two important diseases that are known to have caused significant economic losses to the cattle industry. Accordingly, vaccinations have been recognized as an efficient method to control and prevent both of the above-mentioned diseases. This study aimed to determine the immune response to FMD virus antigens and the recombinant outer membrane protein of HS (rOmpH) of Pasteurella multocida in cattle administered as a comb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 38 publications
0
6
0
Order By: Relevance
“…Peripheral blood mononuclear cell (PBMC) isolation was performed according to the method described in a previous study ( 39 ). Jugular or tail blood samples collected at week 10 of the experiment, that had been kept in ethylene diamine tetraacetic acid (EDTA) tubes (BD Vacutainer, Plymouth, United Kingdom), were diluted with sterilized PBS (pH 7.2; 1:1 dilution) and overlaid on 5 ml of Lymphoprep™ (STEMCELL Technologies, Vancouver, Canada) in 15 ml conical tubes.…”
Section: Methodsmentioning
confidence: 99%
“…Peripheral blood mononuclear cell (PBMC) isolation was performed according to the method described in a previous study ( 39 ). Jugular or tail blood samples collected at week 10 of the experiment, that had been kept in ethylene diamine tetraacetic acid (EDTA) tubes (BD Vacutainer, Plymouth, United Kingdom), were diluted with sterilized PBS (pH 7.2; 1:1 dilution) and overlaid on 5 ml of Lymphoprep™ (STEMCELL Technologies, Vancouver, Canada) in 15 ml conical tubes.…”
Section: Methodsmentioning
confidence: 99%
“…While there was a significant difference between the vaccinated and control groups. In this respect, Muenthaisong et al (2021) prepared and evaluated the P. multocida and foot and mouth disease combined vaccine and concluded that there was a significant difference between the combined vaccine and the P. multocida vaccine. Also, the combined vaccine can be administered safely and produce a degree of immunogenicity with no adverse effects.…”
Section: Discussionmentioning
confidence: 99%
“…Second, FMD was not perceived as the most important livestock disease by village heads, ranked second after HS in both 2016 and 2020. Since HS was the top concern for Laotian smallholders, combined FMD and HS vaccines could be an option to incentivize smallholders to vaccinate animals for both diseases (Muenthaisong et al., 2021). For sustainable FMD control, it is important to maximize participation by smallholders in disease control (Knight‐Jones et al., 2016).…”
Section: Discussionmentioning
confidence: 99%